Oral affections in an ex situ population of marsh deer (Blastocerus dichotomus): a retrospective study (1990-2020) - Borsanelli, Ana Carolina; Saraiva, Júlia R. [UNESP]; Pádua, Daniela B. [UNESP]; Athayde, Flávia R. F. [UNESP]; Vaccari, Juliana [UNESP]; Zanetti, Eveline S.; Dutra, Iveraldo S. [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2022)
Oral diseases are limiting to health, welfare, and conservation practices, especially in the case of endangered animals. In this retrospective study, a survey on oral health-related conditions noted in the clinical records for 261 deer comprised in an ex situ population of the Marsh Deer Conservation Center (CCCP) over 30 years (1990-2020) was carried out. Of these, 49 (18.77%) marsh deer (31 females - 63.27% and 18 males - 36.73%) had clinical oral affections; the affected deer’s mean age was 8.9 years. Logistic regression analysis was performed, and the variable age was significantly associated with the presence of dental affections. Thus, with a change in the age category, a deer had eight times the chance of manifesting oral affections; therefore, age can be considered a risk factor for the manifestation of oral affections in the species. Increased facial volume (65.3%), accumulation of food in the mouth (36.7%), tooth loss (22.4%), fistulas (22.4%), mucosal or palatal lesions (22.4%), tooth wear (20.4%), and tooth root exposure (18.3%) were the most frequently recorded lesions. The relatively high occurrence of oral affections in Blastocerus dichotomus reiterates the importance of oral health care when deer are kept in human care.

As doenças bucais são limitantes para as práticas de saúde, bem-estar e conservação, especialmente no caso de animais ameaçados de extinção. Neste estudo retrospectivo, realizou-se um levantamento sobre condições relacionadas à saúde bucal observadas nos registros clínicos de 261 cervídeos que compunham uma população ex situ do Centro de Conservação do Cervo-do-Pantanal durante um período de 30 anos (1990-2020). Destes, 49 (18,77%) cervos-do-pantanal (31 fêmeas (63,27%) e 18 machos (36,73%)) apresentavam afecções clínicas bucais; e a idade média dos cervídeos afetados foi de 8,9 anos. Realizou-se a análise de regressão logística e a variável idade mostrou associação significativa com a presença de afecções dentárias. Assim, com a mudança de categoria de idade, um cervídeo teve oito vezes mais chances de manifestar afecções bucais; portanto, a idade pode ser considerada como fator de risco para manifestação de afecções bucais na espécie. Aumento de volume facial (65,3%), acúmulo de alimentos na boca (36,7%), perda dentária (22,4%), fístulas (22,4%), lesões nas mucosas ou palatinas (22,4%), desgaste dentário (20,4%) e exposição de raiz (18,3%) foram as lesões mais registradas. A ocorrência relativamente alta de afecções bucais em Blastocerus dichotomus reitera a importância dos cuidados com a saúde bucal quando os cervídeos são mantidos sob cuidados humanos.
Afecções bucais em uma população ex situ de cervos-do-pantanal (Blastoceru dichotomus): um estudo retrospectivo (1990-2020)
Keywords: Oral affections; odontogenic abscess; deer; marsh deer; Blastocerus dichotomus; tooth wear; periodontal disease; Afecções bucais; abscesso odontogênico; cervídeos; cervo-do-pantanal; Blastoceru dichotomus; desgaste dentário; doença periodontal